STRATEGI PENGHIMPUNAN ZAKAT DENGAN SISTEM BARCODE DI MASJID JAMI AL-MUHAJIRIN - Muhammad Rajh Warman Akbar; Efni Anita; Lidya Anggraeni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research is a research on the Strategy of collecting zakat using the barcode system. This research is to obtain information about the Implementation of Zakat Collection Using a QR code (Barcode) at the Jami Al-Muhajirin Alhamdullilah Mosque. Specifically at our Jami Al Muhajirin mosque, there are two methods of receiving zakat fitrah And the first zakat mal method uses a manual system in general where we notify the announcement then after that the people come directly to the mosque to pay zakat in the chronology (implementation) of payment of this method there is a problem In receiving zakat the problem is the range in paying zakat which is only only close people can pay zakat at the Jami Al-Muhajirin mosque Then our second method, we use a digital zakat system in general in implementing transactions using digital zakat we provide applications or use third parties to help us in receiving z At the mosque we use a barcode system where after the barcode is used through the scan me application, the community is directly directed to our account so that the community can pay zakat directly through the account we have provided.